Sulfated Glucuronorhamnoxylan from Capsosiphon fulvescens Ameliorates Osteoporotic Bone Resorption via Inhibition of Osteoclastic Cell Differentiation and Function In Vitro and In Vivo - Kim, Seong Cheol; Kim, Hyeon Jeong; Park, Gi Eun; Lee, Chang Won; Synytsya, Andriy; Capek, Peter; Park, Yong Il (Marine biotechnology, 2022)
Excessive osteoclast differentiation and/or bone resorptive function causes a gradual loss of bone, leading to the pathogenesis of bone diseases such as osteoporosis (OP). In this study, a sulfated glucuronorhamnoxylan polysaccharide (designated SPS-CF) of the green alga Capsosiphon fulvescens was evaluated for anti-osteoporotic activity using osteoclastic cells differentiated from RAW264.7 macrophages by receptor activator of NF-κB ligand (RANKL) treatment and ovariectomized (OVX) female mice as a postmenopausal OP model. With negligible cytotoxicity, SPS-CF (50 μg/mL) significantly suppressed tartrate-resistant acid phosphatase (TRAP) activity, actin ring formation, and expression of matrix metalloproteinase 9 (MMP-9), cathepsin K, TRAF6, p-Pyk2, c-Cbl, c-Src, gelsolin, carbonic anhydrase II (CA II), and integrin β3, indicating that SPS-CF inhibits the differentiation and bone resorptive function of osteoclasts. Removal of sulfate groups from SPS-CF abolished its anti-osteoclastogenic activities, demonstrating that sulfate groups are critical for its activity. Oral administration of SPS-CF (400 mg/kg/day) to OVX mice significantly augmented the bone mineral density (BMD) and serum osteoprotegerin (OPG)/RANKL ratio. These results demonstrated that SPS-CF exerts significant anti-osteoporotic activity by dampening osteoclastogenesis and bone resorption via downregulation of TRAF6-c-Src-Pyk2-c-Cbl-gelsolin signaling and augmentation of serum OPG/RANKL ratios in OVX mice, suggesting that SPS-CF can be a novel anti-osteoporotic compound for treating postmenopausal OP.
Keywords: Animals; Female; ženské pohlaví; kyselá fosfatasa rezistentní k tartarátu; fokální adhezní kinasa 2; Sulfates; sírany; buněčná diferenciace; Chlorophyta; gelsolin; Mice; Osteoporosis; Bone Resorption; faktor 6 asociovaný s receptory TNF; myši; TNF Receptor-Associated Factor 6; Gelsolin; resorpce kosti; Tartrate-Resistant Acid Phosphatase; Cell Differentiation; NF-kappa B; zvířata; osteoporóza; Focal Adhesion Kinase 2